Disinfection protocols to prevent cross-contamination between dental offices and prosthetic laboratories - Ana Carolina Rodrigues Danzi Salvia; Fernanda dos Santos Matilde; Francine Cristina Silva Rosa; Estevão Tomomitsu Kimpara; Antonio Olavo Cardoso Jorge; Ivan Balducci; Cristiane Yumi Koga-Ito (Elsevier, 2013)
Summary: Control of cross-contamination between dental offices and prosthetic laboratories is of utmost importance to maintain the health of patients and dental office staff. The purpose of this study was to evaluate disinfection protocols, considering antimicrobial effectiveness and damage to the structures of prostheses. Solutions of 1% sodium hypochlorite, 2% chlorhexidine digluconate, 50% vinegar and sodium perborate were evaluated. Specimens were contaminated in vitro with standardized suspensions of Candida albicans, Streptococcus mutans, Escherichia coli, Staphylococcus aureus and Bacillus subtilis spores. Disinfection by immersion for 10 min was performed. Final counts of microorganisms were obtained using the plating method. Results were statistically compared by Kruskal-Wallis ANOVA and Dunn's test. The surface roughness of 40 specimens was analyzed before and after 10 disinfection cycles, and results were compared statistically using Student's t test. The solution of 50% vinegar was as effective as 1% sodium hypochlorite and 2% chlorhexidine against C. albicans, E. coli and S. mutans. The sodium perborate solution showed the lowest antimicrobial effectiveness. Superficial roughness increased after cycles in 1% sodium hypochlorite (p = 0.02). Solutions of 1% sodium hypochlorite, 2% chlorhexidine and 50% vinegar were effective for the disinfection of heat-polymerized acrylic specimens. Sodium hypochlorite increased the superficial roughness. Keywords: Cross-contamination, Disinfection, Dental prosthesis, Sodium hypochlorite, Chlorhexidine, Acetic acid